Reaction monitoring reveals poisoning mechanism of Pd2(dba)3 and guides catalyst selection. Issue 96 (16th November 2017) - Colletto, Chiara; Burés, Jordi; Larrosa, Igor
Abstract : We have discovered that the dba ligand in the commonly used Pd2 (dba)3 ·CHCl3 cross-coupling pre-catalyst is susceptible to bis-arylation when used in the presence of aryl iodides. Abstract : We have discovered that the dba ligand in the commonly used Pd2 (dba)3 ·CHCl3 cross-coupling pre-catalyst is susceptible to bis-arylation when used in the presence of aryl iodides. The in situ formed dbaAr2 ligands result in Pd-species with altered catalytic activity. In the case of study, the room temperature C3 arylation of benzo[ b ]thiophenes with aryl iodides, we have observed a marked catalyst deactivation when dba is arylated with electron-deficient aryl iodides, accounting for the poor yields obtained in the C3 arylation reactions with these aryl iodides. Based on these studies, we report a new catalytic system, employing a dba-free Pd catalyst, which allows for the first time the direct C3 arylation of benzo[ b ]thiophenes with electron-deficient aryl iodides at room temperature.